Thermo-Hydro-Mechanical Coupling Model of Unsaturated Soil Based on Modified VG Model and Numerical Analysis - Chen, Peipei; Zhang, Huanwei; Yang, Guangchang; Guo, Zhiguang; Yang, Gaosheng (Frontiers in Earth Science, 2022)
A modified VG model considering both pore ratio and temperature effect is constructed. Based on the wet-thermal elasticity theory and mixture theory, coupled thermo-hydro-mechanical (THM) equations for moisture migration, heat transfer, and deformation in unsaturated soil are derived. The numerical implementation of the coupled theory was implemented by secondary development in the finite element platform. The validity of the established theoretical equation was verified by comparing it with the experimental data. Then the THM coupling response characteristics and internal mechanism of axisymmetric soil samples were numerically analyzed. Study shows that the water in unsaturated soil migrates from high-temperature zone to low-temperature zone under temperature load, and the permeability will change during the process of moisture absorption and dehydration. Particular attention should pay to the reasonable determination of the parameters in the modified VG model for the warming and cooling process of different measurement points during the numerical calculation. The higher the heat source temperature, the greater the saturation at the specific measurement point of the soil sample at thermal stability. The lower the heat source temperature, the shorter the time required for the saturation to stabilize at the specific measuring point. The volumetric strain of unsaturated soil reults from a combination of wet expansion and thermal expansion, which is dominated by wet expansion near the heat source and mainly by thermal expansion far from the heat source. The change of the total displacement with time is dominated by the z-direction displacement, and its change trend along the radial direction is similar to that in the r-direction. The peak of the total displacement curve keeps moving backward with time.